Molecular Shape-Preserving Au Electrode for Progesterone Detection - Fukuto Soyama; Taisei Motomura; Kenshin Takemura (Sensors)
Quantifying progesterone levels in the body is an important indicator of early pregnancy and health. Molecular shape-preserving electrodes have garnered attention in electrochemical biosensors because they can detect targets without the need for expensive enzymes or antibodies. However, some of the currently used methods typically have low electrode durability. Here, progesterone, for which antibodies are typically expensive, was used to develop a molecular shape-preserving electrode using Au to enhance its long-term stability. The physical properties of the electrodes were characterized using scanning electron microscopy (SEM), the electrochemical surface area (ECSA), and cyclic voltammetry (CV). The specific structure of the electrode demonstrated an electrochemical double layer comparable to that of a smooth Au electrode, confirming its high durability. The detection performance was assessed using CV, square wave voltammetry (SWV), and electrochemical impedance spectroscopy (EIS). The current response to progesterone increased in a concentration-dependent manner, but decreased from the saturated state owing to electrodeposition on the surface. Additionally, electrochemical impedance measurements showed high selectivity compared with hormones with similar structures. The fabricated molecular shape-preserving electrode exhibits an excellent durability, stability, and detection performance, confirming its suitability for long-term use. These findings pave the way to new possibilities for electrode fabrication.